Evaluasi Postur Kerja dan Risiko Ergonomi pada Pekerja Administrasi Menggunakan Metode ROSA - Yeti Patiroh; Miftahul Jannah; Neneng Hasanah (Universitas Respati Indonesia, 2026)
Office administration workers generally work in a static sitting position and use computers for long periods of time, thus potentially increasing the risk of ergonomics and musculoskeletal complaints. Workstation ergonomics risk assessment is needed as a basis for improving the working environment. This study aims to describe the level of ergonomic risk based on the assessment of work posture using the Rapid Office Strain Assessment (ROSA) method in PT Z administrative workers. Data were collected through direct observation of workstations using ROSA scoresheets as well as Nordic Body Map (NBM) questionnaires. The analysis was carried out descriptively in the form of frequency and percentage distributions. The results showed that 14 respondents (70.0%) were in the low risk category (score ≤5) and 6 respondents (30.0%) were in the high risk category (score >5). Musculoskeletal complaints are most commonly reported in the shoulders and upper back. Although the majority of workers are in the low-risk category, the proportion of high risks indicates the need for ergonomic interventions, particularly in the arrangement of chairs, monitors, and keyboards and mice, accompanied by work posture education and the implementation of micro-breaks.